2020
DOI: 10.1177/1060028020950726
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telehealth Interventions on Medication Adherence for Patients With Type 2 Diabetes, Hypertension, and/or Dyslipidemia: A Systematic Review

Abstract: Objective: To describe telehealth interventions and determine their effect on medication adherence for patients with type 2 diabetes, hypertension, and/or dyslipidemia. Data Sources: PubMed/MEDLINE, EMBASE, Cochrane, CINAHL Plus, PsycINFO, Academic Search Ultimate, International Pharmaceutical Abstracts, Scopus, Web of Science, WHO Global Index Medicus, association websites, and gray literature were searched from January 1, 1998, to December 31, 2019. Study Selection and Data Extraction: Eligible studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…Patients with diabetes and chronic foot ulcers exhibit poor prognoses in terms of cardiovascular outcomes; telehealth care can be used to provide comprehensive medical treatment beyond wound treatment alone. A previous study [ 28 ] has shown that telehealth care exerts positive effects in terms of disease control, including for hypertension, dyslipidemia, and diabetes, all of which are important predisposing factors for chronic foot ulcer, but chronic foot ulcer is strongly associated with concomitant cardiovascular disease, and therefore, its presence poses an increased risk of cardiovascular events [ 29 ]. In a previous study [ 30 ], we found that patients with cardiovascular disease who were receiving telehealth care had improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes and chronic foot ulcers exhibit poor prognoses in terms of cardiovascular outcomes; telehealth care can be used to provide comprehensive medical treatment beyond wound treatment alone. A previous study [ 28 ] has shown that telehealth care exerts positive effects in terms of disease control, including for hypertension, dyslipidemia, and diabetes, all of which are important predisposing factors for chronic foot ulcer, but chronic foot ulcer is strongly associated with concomitant cardiovascular disease, and therefore, its presence poses an increased risk of cardiovascular events [ 29 ]. In a previous study [ 30 ], we found that patients with cardiovascular disease who were receiving telehealth care had improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the first visits and the visits that are repeated several times for the same problem that is not well understood by the doctor, would be two situations that would require faceto-face visits. Older patients may have more difficulties than younger ones, and these can easier to have the perception of being 'abandoned', and more not indicated drug prescriptions, including antibiotics, can be made [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…265e267 Other studies have demonstrated in persons with both T1D and T2D that telemedicine is associated with improvements in A1C, 184,268e279 reductions in diabetes-related distress, 280 and improvements in medication adherence. 281 The use of telemedicine also has been associated with improved measures of engagement in diabetes self-management among younger individuals with T1D. 282 A 2016 RCT reported lower body fat and improved lipids in its group assigned to telemedicine visits, 274 and the use of telemedicine in women with GDM in a recent RCT resulted in lower A1C, better engagement, and less maternal weight gain.…”
Section: Evidence Basementioning
confidence: 99%